None Herbal Agents as Preventive and Therapeutic Measures for Doxorubicin Induced Hepatotoxicity: A Comprehensive Review - Faezeh Mahmoudi; Sepideh Elyasi (Journal of Pharmaceutical Care, 2022)
Cancer is one of the most common human diseases and a leading cause of human mortality in rencent years. Doxorubicin (DOX) is an important anti-cancer agent belonging to anthracyclines drug category. This chemotherapeutic agent acts against cancer cells through different mechanisms; however, its use is related with numerous acute and chronic dose-related side effects and toxicities including hepatotoxicity. The aim of this study was to conduct a comprehensive review of in vitro, in vivo and any human studies regarding the protective effects of synthetic compounds against DOX-induced liver injury.The search was conducted in embase, PubMed and Scopus databases using the following keywords: “doxorubicin”, “Adriamycin”, “hepatotoxicity”, “liver injury”, “liver damage” and “hepatoprotective” to find experimental and preclinical studies regarding the effects of various compounds on DOX-induced hepatotoxicity. Twenty-one eligible studies to the end of May 2022 finally were reviewed (19 in vivo and 2 both in vivo and in vitro studies). Our results demonstrated that all of these drugs, except acetylsalicylic acid, had considerable hepatoprotective effects against DOX (deferoxamine had a mild effect). In addition, except glutathione, none of the studied drugs and compounds attenuated the antitumor efficacy of DOX treatment. Moreover, no human study was available in this fieild. Altogether, our results demonstrated that most of compounds with anti-apoptosis, anti-inflammatory and antioxidant properties are efficacious against DOX-induced hepatotoxicity and may have potential for being considered for inclusion in the chemotherapeutic regimes of cancer patients, after fully been assessed in well-desgined large clinical trials.